Model-free approach to finding index of refraction values of optical coatings from spectral measurements - Willey, Ronald R (Applied optics. Optical technology and biomedical optics, 2023)
Mathematical models for fitting the refractive index versus the wavelength, such as the Cauchy, Sellmeier, and Drude equations, or physical models, such as the Lorentz model, are commonly used to fit the index properties of measured spectra of optical thin film witness samples for use in the design and production of optical interference coatings. The degree of agreement of the coating reflectance and transmittance with the design when the coatings are produced with these data will depend on the accuracy of the spectral measurements and index fittings. As thin-film coating technology has progressed, many cases are now encountered where no simple model is adequate to fit the actual index dispersion. This work shows an approach to finding the refractive index versus wavelength, which is independent of any mathematical or physical models.Mathematical models for fitting the refractive index versus the wavelength, such as the Cauchy, Sellmeier, and Drude equations, or physical models, such as the Lorentz model, are commonly used to fit the index properties of measured spectra of optical thin film witness samples for use in the design and production of optical interference coatings. The degree of agreement of the coating reflectance and transmittance with the design when the coatings are produced with these data will depend on the accuracy of the spectral measurements and index fittings. As thin-film coating technology has progressed, many cases are now encountered where no simple model is adequate to fit the actual index dispersion. This work shows an approach to finding the refractive index versus wavelength, which is independent of any mathematical or physical models.